Oral history theory - Abrams, Lynn (Routledge, 2010)
Oral history is increasingly acknowledged as a key tool for anyone studying the history of the recent past. This book is the first to provide a comprehensive and systematic overview of oral history theory in an accessible format. The book is structured around key themes, including the peculiarities of oral history, the study of the self, subjectivity and intersubjectivity, memory, narrative, performance and power. Each chapter provides a clear and user-friendly explanation of the various theoretical approaches, illustrates them with examples from the rich field of published oral history, and makes suggestions for the practicing oral historian. There is also a glossary of key terms and concepts. Combining the study of theoreticians with the observations of practitioners, and including extensive examples of oral history work from around the world, this book constitutes the first integrated explanation of oral history theory. It will be invaluable to experienced and novice oral historians, professionals, and students who are new to the discipline.